Optimising Data Utilisation in Lexicography: The Case of the Khoekhoegowab Dictionary - Haacke, Wilfrid Heinrich Gerhard (Lexikos, 2012)
Despite of rapid progress in Southern Africa in the direction of multifunctionality of lexical databases through the advent of generic lexicographic software, a considerable number of lexicographic projects — especially in Khoe and Saan languages — still use or have recently used a word processor with the sole objective of compiling a printed dictionary. Hence the present paper expounds on the case of the Khoekhoegowab Dictionary Project, how in the early 1990s some off-the-shelf DOS-based database software was configured as part of a "home-grown" custom-made dictionary writing system. It is demonstrated in a non-technical way that the use of a structured database with fully-fledged retrieval facilities allows for the far-reaching elimination of human error in a dictionary, for the automatisation of processes like language reversal and sorting, and, finally, for the significantly enhanced usability of the data for purposes other than fixed media dictionary compilation. Compiling a dictionary without extensive query facilities as offered by tabular databases, is argued to be a lost opportunity, as it should be possible to utilise lexicographic data for more than just lexicography. By 2010 the data was accommodated in open source software to ensure its optimal survival in digital form for future use. Keywords: automatisation; compilation software; data retrieval; database configuration; database report; flat-file database; form; information generation; khoekhoe; khoesaan dictionaries; lexicography; lookup facilities; multifunctionality; query facilities; retrieval facilities; software; tones